Remote Inspection, Measurement and Handling for Maintenance and Operation at CERN. (6th November 2013) - Kershaw, Keith; Feral, Bruno; Grenard, Jean-Louis; Feniet, Thierry; De Man, Sven; Hazelaar-Bal, Cathelijne; Bertone, Caterina; Ingo, Ruehl
Remote inspection, measurement and handling techniques are under development for use in CERN's particle accelerator facilities to reduce radiation exposure of personnel and reduce facility downtime when scheduled maintenance or breakdown repairs are needed. This paper gives an explanation of the potential benefits to CERN of remote inspection, measurement and handling along with a brief history of remote handling work at CERN. Recent projects are then described, covering the development work and operations forming part of CERN's recent remote inspection, measurement and handling activities.